Unraveling the Anticancer Components of Centipeda minima and their Cellular Targets in Human Cancers. Issue 1 (2nd January 2022) - Maqbool, Muhammad Faisal; Ashaq, Aisha; Maryam, Amara; Khan, Muhammad; Ali, Muhammad Akhtar; Shakir, Hafiz Abdullah; Gul, Sameena; Shakoori, Farah Rauf; Irfan, Muhammad; Ara, Chaman
Abstract: Centipeda minima ( C. minima ), is a medicinally important herb commonly called "Sneeze Weed" and widely distributed in humid areas. In China, Malaysia, and Nepal, it is used in folk medicines for the treatment of rhinitis, nasopharyngeal carcinoma, and respiratory disorders, it also exhibits antibacterial, antioxidant and antiprotozoal activity. Recently it is discovered that various bioactive molecule of C. minima has strong potential to be used in the treatment of various neoplasms. Thus, in this review, we aim to summarize and discuss various cellular targets and anticancer mechanisms of different bioactive components of C. minima. The pool of multiple studies suggested that various components of C. minima reduce cell growth, arrest cell cycle at various checkpoints and thereby induce apoptosis in different cancer cells via intrinsic and extrinsic apoptotic pathways. Moreover, these bioactive molecules also modulate different signaling pathways implicated in tumorigenesis including STAT3, NF-κB, ERK1/2, MMPs and AKT. In parallel to antiproliferative effect of C. minima, it also has antimetastatic and antineoplastic activities. A pile of literature clearly supported the anticancer activity of various components of C. minima against multiple human cancer cell lines. Thus, this review will be a milestone in the design and conduct of future research for the development of novel plant-based chemotherapeutics from C. minima .